Nuclear energy now: Why the time has come for the world's most misunderstood energy source - Herbst, Alan M (John Wiley & Sons, 2013)
In this book energy experts Alan Herbst and George Hopley provide you with a balanced look at the benefits and drawbacks associated with this effective alternative to traditional energy sources, and discuss why the time has come for the United States to revitalize its nuclear generation assets.